Persistent inequalities in child undernutrition: evidence from 80 countries, from 1990 to today - Bredenkamp, Caryn (Int J Epidemiol, 2014)
Background: Global progress in reducing the burden of undernutrition tends to be measured at the population level. It has been hypothesized that population-level improvements may mask widening socioeconomic inequalities, but little attempt has been made to assess whether this is true. Methods: Original data from 131 demographic health surveys and 48 multiple indicator cluster surveys from 1990 to 2011 were used to examine trends in socioeconomic inequalities in stunting and underweight, as well as the relationship between changes in prevalence and changes in inequality, in 80 countries. Socioeconomic inequality is measured using the corrected concentration index. Results: Countries with a higher prevalence of stunting tend to have larger socioeconomic inequalities in stunting (Spearman rank correlation = −0.27 P = 0.014). In most countries, there has been no change in inequality in stunting: in 31 out of 53, the 90% confidence intervals around the changes overlap the zero value. In the remaining 22, there was a reduction in inequality in 11 and an increase in 11. The distributional patterns underlying the summary inequality statistics vary considerably across countries, but in most there have been considerable gains to the poorest quintile. Conclusions: Reductions in the prevalence of undernutrition have generally not been accompanied by widening inequalities. However, inequalities have also not been narrowing. Rather, the picture is one of a strong persistence of existing inequalities. In addition, there are different distributional patterns underlying changes in the summary indices of inequality which will need to be taken into consideration in designing programmes to reach the poor.